The role of lysyl oxidase-like 1 (LOXL1) in exfoliation syndrome and glaucoma - Schlötzer-Schrehardt, Ursula; Zenkel, Matthias (Experimental Eye Research, 2019)
Exfoliation syndrome (XFS) is an age-related systemic disease that affects the extracellular matrix. It increases the risk of glaucoma (exfoliation glaucoma, XFG) and susceptibility to diseases of elastin-rich connective tissues. LOXL1 (lysyl oxidase-like 1) is still recognized as the major genetic effect locus in XFS and XFG in all populations worldwide, although its genetic architecture is incompletely understood. LOXL1 is a key cross-linking enzyme in elastic fiber formation and remodeling, which is compatible with the pathogenetic concept of XFS as a specific type of elastosis. This review provides an overview on the current knowledge about the role of LOXL1 in the etiology and pathophysiology of XFS and XFG. It covers the known genetic associations at the LOXL1 locus, potential mechanisms of gene regulation, implications of LOXL1 in XFS-associated fibrosis and connective tissue homeostasis, its role in the development of glaucoma and associated systemic diseases, and the currently available LOXL1-based in vivo and in vitro models. Finally, it also identifies gaps in knowledge and suggests potential areas for future research.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Elastic fibers; Exfoliation glaucoma; Exfoliation syndrome; Extracellular matrix; LOXL1; Lysyl oxidase-like 1; Pseudoexfoliation syndrome